Element fini de coque a trois nreuds pour le calcul des structures minces en grandes deformations - Boisse, Philippe; Daniel, Jean-Luc; Gelin, Jean-Claude (European Journal of Computational Mechanics, 1993)
A co three node shell finite element well suited to calculations where geometrical non-linearities are taken into account is proposed. The element is based on isoparametric continuum based kinematics and shear locking is avoided by using an inJerpolation of the tranverse shear strain components. A materia/frame related to the element side is considered to define the nodal values of tranverse shear strains. The modifications concern the linear and non-linear parts of the strains. They are taken into accounJ at any level of the Newton scheme and in particular to calculate the initial stress matrix. The element works using a single set of Gauss points along the normal at the center to be very efficient from the computational point of view. A set of examples show a correct efficiency in linear calculations and very good performances in non-linear tests. A numerical simulation of sheet metal forming is described and the element appears to be well adapted for these types of calculations.